Facial Reconstruction after Surgical Excision of Basal Cell Carcinoma - Anas H. Abed; Mohammed Kh. Abduljalel; Kamal Turki Aftan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background and Aim of Study: The aim of this study was to evaluate the outcomes of different facial flapsused for reconstruction after surgical excision of basal cell carcinoma.Patients and Methods: Patients with BCC of the facial area were 128 cases. The cases were treated, andfollowed up between January 2012 and April 2018. Results: There was a single case of tumor recurrencein the frontal area. Also scar formation in female patient over 60 years old was noted. The case of scarformation was notes after frontal flap which used for treatment of nasal defect.Otherwise, there was no patient with any complications (like infective wound, keloid, scar formation,ischemia, or necrotic tissues), have been seen among the rest of the cases at the end of our study on 2020. Inall male cases that treated with skin graft after excision of the tumor in frontal area which was 8 patients; atthe end of follow up period, the color of skin and tissue harmony was coordinated.Conclusion: No specific flap or graft can be done for all the types of BCC, we should choose the mostappropriate flap or graft. Recurrent ratio was very low.